LTBP2 mutation may cause mitral valve prolapse. (3rd October 2022) - Durst, R
Abstract: Background: Mitral valve prolapse (MVP, MIM 157700) is a very common cardiac disorder occurring in 2.4% of the general population. MVP is characterized by myxomatous degeneration resulting in valve thickening, prolapsing and regurgitation. MVP results in mitral regurgitation, arrhythmias, bacterial endocarditis, congestive heart failure and sudden death. Familial studies of MVP suggest an autosomal dominant mode of inheritance with incomplete penetrance. We are wokring on defining the genetic causes of MVP. Methods and results: We identified an MVP family with an LTBP-2 Val1506Met rare mutation (minor allele frequency of 0.0001) segregating with the MVP (LOD score of 1.5 out of a maximal potential of 2.6). LTBP2 is an excellent candidate gene for MVP because it regulates TGFβ signaling activity, shown to be disrupted in Marfan's syndrome mitral valvulopathy. High prevalence of MVP was reported in relatives of patients with Weill-Marchesani syndrome, caused by LTBP2 mutations. We then generated two strains of mice using CRISPR technology. A complete knockout (deletion of the first exon) and a knock in mouse. Nineteen mice were dissected so far (figure 3). None of the wt mice (n=8) demonstrated myxomatous degeneration. Of the 11 mice with mutation, 8 homozygote for deletion and 3 homozygote for the human mutation, 8 demostrated myxomatous Degeneration by histology (1 knockin mouse ∼70% pentrance in male mice, p=0.001, Fisher exact test). The pathologist that read the studies was blinded to the genotype. Echocardiography of theses mice demonstrated findings consistant with MVP (deviation of the leaflets above the annluar line in parasternal long axis view) in 50% of affected mice and not in controls Conclusion: We demonstrated that an LTBP2 mutation is segretating in a family with MVP. LTBP2 mutation mice model demonstrated myxomatous degeneration of the valve. Thus, LTBP2 may be an MVP causing gene Funding Acknowledgement: Type of funding sources: Public hospital(s).